Rumah sakit Zending Mojowarno di Jombang 1894-1942 - Kusuma, Ananta Dharma; Hudiyanto, R. Reza (Historiography: Journal of Indonesian History and Education, 2024)
Abstract This research was created to give readers an overview of the history of the Mojowarno Hospital during the Dutch colonial era. The topics discussed in this article include the development process of the Zending Mojowarno Hospital in 1894-1942 and the resulting impact of the development of the Zending Hospital for the people of Jombang. In making this research the authors used historical perspective on health in explaining past events. The study uses historical methods which consist of five stages, namely topic selection, heuristics, verification, interpretation, and historiography. The results of this study indicate that the development of hospitals has positive implications for society such as the inclusion of Western medicine in the midst of traditional medicine, the presence of paramedical education who plays an active role in improving public health services, eradicating disease, and increasing public trust in Western methods due to the efficacy of the care provided. Abstrak Penelitian ini dibuat untuk memberi gambaran kepada pembaca tentang sejarah Rumah Sakit Mojowarno di masa pemerintahan kolonial Belanda. Topik yang dibahas dalam artikel ini diantaranya mengenai proses perkembangan Rumah Sakit Zending Mojowarno pada 1894-1942 serta dampak yang dihasilkannya dari adanya perkembangan rumah sakit zending bagi masyarakat Jombang. Dalam pembuatan penelitian ini penulis menggunakan perspektif sejarah kesehatan dalam menerangkan peristiwa masa lampau. Penelitian menggunakan metode sejarah yang terdiri lima tahapan yakni pemilihan topik, heuristik, verifikasi, interpretasi, dan historiografi. Hasil penelitian ini menunjukkan bahwa perkembangan rumah sakit membawa implikasi positif bagi masyarakat seperti masuknya pengobatan Barat di tengah-tengah pengobatan tradisional, hadirnya pendidikan paramedis berperan aktif dalam meningkatkan pelayanan kesehatan masyarakat, pemberantasan penyakit, serta adanya peningkatan kepercayaan masyarakat terhadap metode Barat akibat kemujaraban perawatan yang diberikan.